Accuracy of faecal immunochemical testing in patients with symptomatic colorectal cancer. Issue 6 (18th September 2020) - Khan, A A; Klimovskij, M; Harshen, R
Abstract: Background: The aim of this study was to determine the diagnostic accuracy of the faecal immunochemical test (FIT) for detecting colorectal cancer in symptomatic patients. Methods: This was a prospective study of patients with bowel symptoms. Stool samples were collected during rectal examination. The HM-JACKarc assay (Kyowa Medex, Tokyo, Japan) was used to quantify faecal haemoglobin (Hb); positive results were those with at least 10 μg Hb/g faeces. Two-by-two tables and receiver operating characteristic (ROC) curve analysis were used to determine diagnostic accuracy; χ 2 and Mann–Whitney U tests were used to compare other parameters. Results: A total of 928 patients were included (M : F ratio 1 : 1·5; median age 72 (i.q.r. 64–80) years). The overall prevalence of colorectal cancer was 5·1 per cent. The FIT had sensitivity of 85·1 per cent, specificity of 83·5 per cent, positive predictive value of 22·6 per cent and negative predictive value of 99·0 per cent. ROC analysis of FIT for diagnosing colorectal cancer gave an area under the curve value of 0·89 (95 per cent c.i. 0·84 to 0·94). Significant bowel pathology was detected more frequently in FIT-positive patients (35·1 per cent versus 7·1 per cent in FIT-negative patients; P < 0·001). There were sex differences in FIT positivity (23·7 per cent in men versus 17·4 per cent in women; P = 0·019); the sensitivity of FIT for colorectal cancer in women was also low. False-negative FIT results were found mainly in women referred with iron-deficiency anaemia, who were found to have caecal cancer. Conclusion: FIT effectively excluded colorectal cancer in symptomatic patients. Integration of FIT into the diagnostic pathway for colorectal cancer would direct resources appropriately to patients with a greater likelihood of having the disease. Graphical Abstract: This study confirmed that the faecal immunochemical test (FIT) has a high diagnostic accuracy for detecting colorectal cancer in symptomatic patients. FIT can be used to triage 2-week-wait colorectal referrals. FIT tests to streamline pathways